2020
DOI: 10.1097/gox.0000000000003116
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Implants among Breast Reconstruction Patients in Montreal

Abstract: Background: In light of the recent surge of media coverage and social media influence regarding breast implants, it is essential to understand patients’ concerns and misconceptions so that we can better serve them. Methods: The authors designed a survey study for assessing the awareness and perception of patients toward breast implant–associated anaplastic large cell lymphoma (BIA-ALCL) and breast implant illness (BII). In total, 130 patients presenting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
2
12
0
1
Order By: Relevance
“…Thus, it is essential to educate patients about the common signs and symptoms of complications associated with breast implants. [ 9 ] In the present study, most participants (59%) were not aware of capsular contracture. Of the participants who were aware of capsular contracture, most had heard about it from social media (39%), followed by their physician (32%).…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Thus, it is essential to educate patients about the common signs and symptoms of complications associated with breast implants. [ 9 ] In the present study, most participants (59%) were not aware of capsular contracture. Of the participants who were aware of capsular contracture, most had heard about it from social media (39%), followed by their physician (32%).…”
Section: Discussionmentioning
confidence: 57%
“…[ 11 ] In the present study, most participants (67%) were unaware of BIA-ALCL. In contrast, in a similar study conducted by Bouhadana et al ,[ 9 ] only 16% of the participants were unaware of BIA-ALCL. This indicates the lack of awareness among the Saudi population and the importance of raising awareness.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“… 7 On the contrary, Bouhadana et al reported that 70% of their sample knew about BIA-ALCL, mainly through newspapers, television, and physicians. 8 Their findings could be explained by the fact that more than 80% of the recruited population had a background of breast cancer and underwent reconstruction with implants.…”
Section: Discussionmentioning
confidence: 99%